Planning for plurality of streets: a spheric approach to micromobilities. Issue 1 (2nd January 2022) - Bahrami, Farzaneh; Rigal, Alexandre
ABSTRACT: Micromobilities have proliferated over recent years, enabled by technological advances. Together they present opportunities to flip urban mobility into a new system, beyond car dominance, towards inclusivity, diversity, and sustainability. We propose a theoretical framework to compare these vehicles and assess their potential in urban space. The notion of Sphere and the conceptions associated with it guide the development of our framework, enabling classification and analysis of micromobilities evaluating their impacts on their immediate environment and their capacities to cohabit with other modes of transport. The discursive analysis of 53 interviewees is used to corroborate our framework, particularly investigating the spheric characteristics of mobility experiences using various modes in diverse urban settings in Switzerland. This paper first adopts a historical perspective, exploring the emergence of vehicular innovations that developed in response to the early problems faced by the car system in cities and traces the evolution of these innovations through to the recent proliferation of micromobilities. Then the framework and interviews are described. Finally, we discuss the socio-spatial implications of the classification of transport modes based on their spheric properties, with a view to enabling new perspectives and potentially new socio-spatial relations towards the plurality of streets.